Vedolizumab Drug Level Correlation With Clinical Remission, Biomarker Normalization, and Mucosal Healing in Inflammatory Bowel Disease. Issue 3 (24th August 2018) - Al-Bawardy, Badr; Ramos, Guilherme Piovezani; Willrich, Maria Alice V; Jenkins, Sarah M; Park, Sang Hyoung; Aniwan, Satimai; Schoenoff, Shayla A; Bruining, David H; Papadakis, Konstantinos A; Raffals, Laura; Tremaine, William J; Loftus, Edward V
Abstract: Background/Aims: The clinical utility of vedolizumab (VDZ) trough levels (VTLs) in inflammatory bowel disease (IBD) is not well defined. The aims of this study are to determine the median VTLs and frequency of detected antibodies, the correlation of VTLs with C-reactive protein (CRP) and mucosal healing (MH), and the change in clinical management based on VTLs. Methods: A cross-sectional study of IBD patients treated with VDZ with VTLs checked between July 1, 2016, and March 1, 2017, was conducted. Mucosal healing was defined as absence of mucosal ulcers in Crohn's disease (CD) and Mayo endoscopic score ≤1 for ulcerative colitis (UC). Normal CRP was defined as ≤8 mg/L. Results: A total of 171 patients (62% CD, 31% UC, 7% indeterminate colitis) were included. Median VTLs was 15.3 ug/mL (range, 0–60), and 1 patient had detectable antibodies to VDZ. Patients with a normal CRP had a median VTLs of 17.3 ug/mL vs 10.7 ug/mL in high CRP patients ( P = 0.046). This was noted in CD (20.3 vs 10.4 ug/mL; P = 0.005) but not in UC patients (14.4 vs 20.8; P = 0.72). Mucosal healing was achieved in 35% of patients (37 of 105); among these, median VTLs was 13.7 ug/mL vs 16.1 ug/mL in patients who did not achieve MH ( P = 0.64). Vedolizumab trough levels resulted in a change in clinical management in 73%. Conclusions: Our cohort showed a low rate of immunogenicity to VDZ and an association between VTLs and CRP in CD but not in UC patients. No relationship between VTLs and MH was detected. Vedolizumab trough level measurements altered management in approximately three fourths of patients.